Dataset of biological community structure in Deepor Beel using eDNA approach–A RAMSAR wetland of Assam, India - Nikita, Rajkumari; Ghosh, Anwesha; Yash; Kumar, Chakresh; Mandal, Arkaprava; Saini, Nirupama; Dubey, Sourabh Kumar; Gogoi, Kalpajit; Rajts, Francois; Belton, Ben; Bhadury, Punyasloke (Elsevier, 2024)
Deepor Beel, located in the state of Assam in India, is a Wetland of International Importance with a Wildlife Sanctuary and is the only RAMSAR site in the state. Though of invaluable ecological significance, the wetland is facing anthropogenic stressors, leading to rapid degradation of ecological health. In December 2022, surface water was collected from six stations of Deepor Beel to elucidate biological communities using the eDNA approach. At the time of sampling, in-situ environmental parameters were measured in triplicates. The dissolved nutrients and concentrations of metals and metalloids were estimated using UV–Vis Spectrophotometry and ICP-MS approaches respectively. The study revealed a high concentration of dissolved nitrate in the surface water. High-throughput sequencing using Nanopore sequencing chemistry in a MinION platform indicated the overwhelming abundance of Moraxellaceae (Prokaryotes) and Eumetazoa (Eukaryotes). The abundance of Cyprinidae were also encountered in the studied wetland reflecting the biodiversity of fish populations. High nitrate along with elucidated microbial signals are crucial to designate ecological health status of Deeper Beel. This study is aimed at generating baseline information to aid long-term monitoring and restoration of the Deepor Beel as well as the first comprehensive assessment of a RAMSAR Site located in northeast of India.